MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TALKING PADA MATERI PERUSAHAAN DAGANG DI KELAS XII IPS 1 SMA NEGERI 2 PEKANBARU: Improving Student Learning Outcomes by Using Active Guided Note Talking Strategies in Trading Company in Class XII IPS 1 SMA Negeri 2 Pekanbaru - Angreta Angreta (Perspektif Pendidikan dan Keguruan, 2019)
Teaching the learning materials of trading companies the author found that only a few students were active in expressing their opinions, as well as asking questions. Students are even passive, reluctant to ask the teacher if they do not understand the material being taught, unfocused and sleepy when the learning takes place so that the learning outcomes obtained by students on the subject of trading companies are on average 78. Students who complete only about 10 students and 24 students did not complete, while the minimum completeness criteria (KKM) were determined 82. To overcome the problem of lack of attention and activeness of students, the authors tried to apply Using the Guided Note Talking Type Active Learning Strategy to the Material of Trading Companies. This type of research is classroom action research. As for the object of this research are students of class XII IPS 1 Pekanbaru 2 High School. The method of data collection in this study used tests, observation and documentation. The research instrument is a formative test. The results showed an increase in accounting learning outcomes of students of class XII IPS 1 Pekanbaru 2 High School, amounting to 34 students. The application of active Guided Note Talking learning strategies can improve student learning activities. Where the teaching and learning process can be carried out pleasantly so that students can be motivated to learn. The application of active Guided Note Talking learning strategies can improve student learning outcomes with a percentage of the first cycle of 50%, and a second cycle of 85.29%, and the average learning value of students in cycle I 84.38 and cycle II 90.5.Keywords: Learning Outcomes, Economics, Accounting, Talking Guided Note Type Active Learning Strategies